The Test of Relationship Between Government Expenditure and Economic growth of Lao PDR - XAYSAMPHANH , Khamsavang; CHANTHAVONE, Thongphanh; PHOUNNALY, Phayvanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The purpose of this study is to examine 1) relationship between government expenditure and economic growth of Lao PDR in short-term and long-term period, and 2) the Granger Causlity between the government expenditure and economic growth of Lao PDR. The research target group is monetary policy instruments of Lao PDR government, and the instrument used to collect data is annual economic report of the Bank of the Lao PDR and Asian Development Bank in the period of 1986-2020 (35 year), including government expenditure, GDP and GDP per capital. The research tested a relationship between the government expenditure and economic growth of Lao PDR for long-term period by applying the Engle and Grenger method and short-term through the Error Correction Mechanism. And the Granger Causality test for variables relationship. The results of unit root test found that all of government expenditure variables, GDP variables and GDP per capital are non-stationary at I (0) and characterization of stationary by I (1) process at the 1% level. Therefore, 1) relationship between government expenditure and economic growth of Lao PDR, the results indicate that the government expenditure and GDP of Lao PDR has bidirectional relationship in the short-term and long-term period, which the short-term adjustment of government expenditure deviates to the long-term equilibrium with a velocity of 63.09%, and short-term adjustment of GDP deviates to the long-term equilibrium with a velocity of 40.52%. Moreover, the results indicate that the government expenditure and GDP per capital of Lao PDR has unidirectional relationship in the short-term and long-term period, which the short-term adjustment of government expenditure deviates to the long-term equilibrium with a velocity of 55.05%, and short-term adjustment of GDP deviates to the long-term equilibrium with a velocity of 37.42%. 2) The results of Granger Causality test show that the growth of GDP and the growth of government expenditure have bidirectional relationship in the short term, as well. Furthermore, the results of Granger Causality test indicate that the growth of GDP per capital and government expenditure have bidirectional relationship in the short term.